The tumor stroma influences immune cell distribution and recruitment in a PDAC-on-a-chip model - Geyer, Marlene; Gaul, Lisa-Marie; D`Agosto, Sabrina Luigia; Corbo, Vincenzo; Queiroz, Karla (Frontiers in Immunology, 2023)
The dense tumor stroma of pancreatic ductal adenocarcinoma (PDAC) and its secreted immune active molecules provide a barrier for chemotherapy treatment as well as for immune cell infiltration to the tumor core, providing a challenge for immunotherapeutic strategies. Consequently, the investigation of processes underlying the interaction between the tumor stroma, particularly activated pancreatic stellate cells (PSCs), and immune cells may offer new therapeutic approaches for PDAC treatment. In this study, we established a 3D PDAC model cultured under flow, consisting of an endothelial tube, PSCs and PDAC organoids. This was applied to study the role of the tumor microenvironment (TME) on immune cell recruitment and its effect on partly preventing their interaction with pancreatic cancer cells. We observed that stromal cells form a physical barrier, partly shielding the cancer cells from migrating immune cells, as well as a biochemical microenvironment, that seems to attract and influence immune cell distribution. In addition, stromal targeting by Halofuginone led to an increase in immune cell infiltration. We propose that the here developed model set ups will support the understanding of the cellular interplay influencing the recruitment and distribution of immune cells, and contribute to the identification of key players in the PDAC immunosuppressive TME as well as support the discovery of new strategies to treat this immune unresponsive tumor.